The propulsion of call service in palliative oncology care in the COVID-19 pandemic (Research, Society and Development, 2022)
Objective: to describe the experience of a home care service to ensure continuity of care for patients in exclusive palliative cancer care during the pandemic. Methodology: qualitative, descriptive study, experience report type. The setting was a Federal Hospital, located in Rio de Janeiro, Brazil. Development: during the COVID-19 pandemic, strategies were developed to improve tele-service in health, a tool that was already used in the service in an incipient way and that started to assume greater importance in the service's routines. The paths adopted were directed not only to meet spontaneous demands, but also to carry out an active search for symptomatic patients, allowing for the screening of cases by severity. Final considerations: Although several challenges were encountered, such as the insufficiency of professionals and lack of technological support, among others, some actions promoted the reception and monitoring of patients remotely and safely. It is concluded that the incorporation of teleservice has contributed to the care of patients monitored by this service with benefits that exceed the needs of the pandemic period.